(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The paper focuses on designing and developing a user interface to help out the community in making a secure and also a better use of ATM cards using virtual ATM card application. ATM cards are essential in everyday life. Millions of ATM transactions take place in a day. ATM cards are security less when it is lost or stolen. In ATM cards, the PIN is essential and the user should systematically change the PIN. The PIN should not be shared with anyone. If a PIN is known to the hacker then it very easy to use the ATM card. To resolve this the Virtual ATM cards help more. The number of ATM card changes after every transaction. This helps the user to keep the ATM card number more securely for efficient cardless transactions. The virtual ATM card project is implemented using web technology and Android Studio software using java language. Implementation can be done in 3 phases. The first phase involving the design of the GUI for the end-user to scan the QR image in the ATM, the second phase deals with the implementation of a generation of 16-bit Random digit and third phase involves in connection to the server by entering the pin, the bank server checks the authentication and process the transaction. If the user using the online payment for the transaction, then the user requests the bank server for the ATM card number in the Application. After the authentication, the bank server provides the card number to the user. After the transaction, the card number automatically will be destroyed and creates a new card number for the user. The PIN can change, or it can be auto-generated PIN by bank server so that the security can be improved. Maintenance and further development of the application, as well as the feedback provided by the end-users, are encouraged.